2020
DOI: 10.1371/journal.pone.0231044
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of B-Mode ultrasound and Hepatorenal Index for graduation of hepatic steatosis in patients with chronic liver disease

Abstract: Background/Aims The aim of our study was to evaluate the diagnostic accuracy of B-Mode ultrasound and Hepatorenal Index (HRI) by high-end devices for the detection and classification of hepatic steatosis in patients with various causes of chronic liver disease (CLD). Methods We retrospectively enrolled patients with CLD who underwent liver biopsy and baseline ultrasound between March 2016 and May 2019. Sonographic graduation of steatosis (0˚-III) using B-Mode criteria and HRI were correlated with the histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
2
34
2
5
Order By: Relevance
“…This procedure has a high specificity for the presence of fatty liver disease but the sensitivity is insufficient for minor changes to the hepatocytes (steatosis percentage < 20 %) [20]. A quantitative determination of the sound attenuation or a computational comparison of the kidney/liver parenchyma can provide more precise results [21]. However, for steatosis screening, methods based on magnetic resonance imaging are superior to ultrasound-based methods [22].…”
Section: Diagnosing Steatosismentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure has a high specificity for the presence of fatty liver disease but the sensitivity is insufficient for minor changes to the hepatocytes (steatosis percentage < 20 %) [20]. A quantitative determination of the sound attenuation or a computational comparison of the kidney/liver parenchyma can provide more precise results [21]. However, for steatosis screening, methods based on magnetic resonance imaging are superior to ultrasound-based methods [22].…”
Section: Diagnosing Steatosismentioning
confidence: 99%
“…As a result, both the liver contour and the visualization of the hepatic vessels, particularly thin-walled hepatic veins, are affected. Therefore, a number of authors recommend the graduation of the degree of steatosis on the basis of the attenuation of the sound signal on the B-mode image [21,24]: ▪ Grade 1 -Increased parenchymal echogenicity without the signal intensity being affected ▪ Grade II -Additional attenuation of the signal intensity while the visibility of the dorsal liver contour is maintained ▪ Grade III -Complete signal attenuation (signal loss) in the steatotic liver parenchyma. Liver contours far from the transducer and the diaphragm can no longer be differentiated.…”
Section: Diagnosing Steatosismentioning
confidence: 99%
See 1 more Smart Citation
“…After examining the full text of these publications, we excluded four studies owing to unsatisfactory inclusion criteria or unsatisfactory outcome measures [Table 2]. As a consequence of this selection strategy, twelve observational studies [18,[24][25][26][27][28][29][30][31][32][33][34] comparing the diagnostic accuracy of ultrasonography to liver histology were included in the meta-analysis and were assessed for quality (as summarized in Table 3). These studies included 2921 middle-aged participants (mean age 45 ± 7 years; mean BMI 29 ± 9 kg/m 2 ), 1710 (58.5%) of whom had ≥ 5% histologically defined HS.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Studies have shown that the diagnosis of moderate or severe grades of liver steatosis by ultrasound is characterized by sensitivity and specificity rates of 80–91% and 87–98%, respectively. Nevertheless, these values drop to as low as 53% and 77%, respectively, when detecting steatosis of any grade [ 68 , 69 , 70 , 71 , 72 ].…”
Section: Ultrasound Based Techniquesmentioning
confidence: 99%